Suicidal ideation, plan, and attempt among men who have sex with men in Nepal: Findings from a cross-sectional study. - Kiran Paudel; Kamal Gautam; Prashamsa Bhandari; Jeffrey A Wickersham; Manisha Dhakal; Sanjay Sharma; Krishna C Poudel; Toan Ha; Roman Shrestha (Public Library of Science (PLoS), 2023)
Men who have sex with men (MSM) are at increased risk for suicide, with a much higher prevalence of suicidality than the general population. While there is a growing interest in the identification of risk factors for suicidal behaviors globally, the understanding of the prevalence and risk factors for suicidal behaviors among MSM in the context of low- and middle-income countries is almost non-existent. Therefore, this study aimed to investigate suicidal ideation, plan, and attempts, and related factors among MSM in Nepal. A cross-sectional respondent driven survey was conducted on 250 MSM between October and December 2022. Bivariate and multivariable logistic regression was used to evaluate independent correlates of suicidal behaviors of MSM. Overall, the lifetime prevalence of suicidal ideation, plans, and attempts among MSM in this study were 42.4%, 31.2%, and 21.6%, respectively. MSM with depressive symptoms (aOR = 5.7, 95% CI = 2.4-14.1), advanced education (higher secondary and above; aOR = 2.9, 95% CI = 1.4-6.1), and smoking habit (aOR = 2.5, 95% CI = 1.2-5.3) were at increased risk for suicidal ideation. Similarly, those with depressive symptoms (aOR = 2.2, 95% CI = 1.1-4.8) and advanced education (aOR = 2.7, 95% CI = 1.2-5.7) were more likely to plan suicide, whereas young MSM were significantly more prone to attempting suicide (aOR = 2.7, 95% CI = 1.3-5.8). Interestingly, MSM with moderate to severe food insecurity were 2-3 times more likely to think about, plan, or attempt suicide (ideation: aOR = 3.5, 95% CI = 1.6-7.7; plan: aOR = 3.7, 95% CI = 1.6-8.3; attempt: aOR = 2.2, 95% CI = 1.1-4.6). The results suggest the importance of early assessment of suicidal behaviors among MSM and the need for tailored interventions to simultaneously address mental health problems and food insecurity to reduce suicide-related problems among Nepalese MSM.